Práticas autolesivas de risco: uma análise dos canais do Youtube do Everson Zoio - Rogério, Antonio Dhennis Maia (2024)
Presents a case study on two channels of the YouTuber Everson Zoio, a young Brazilian who produces videos featuring "high-risk self-harming practices." This term is suggested in this dissertation for the set of contents commonly referred to as challenges, games, and dangerous activities shared online and reproduced offline. The study aimed to analyze the violations of platform guidelines and the rights of children and adolescents in the productions involving risky situations published on Everson Zoio's channels, exploring the contradictions between the platform's guidelines and the practices it hosts. Finally, the research addresses the relationship between this content and the democratization of communication and digital platforms, also highlighting existing tensions and successful examples of platform regulation in other parts of the world.